FIGURATIVE LANGUAGE IN THREE EMINEM'S SONGS - Lenno Albion; Mia Rahmawati Yuwita (MAHADAYA: Jurnal Bahasa, Sastra, dan Budaya, 2022)
Language can not be taken as it is, in semantics, there is figurative language that is used as an expression and not by its literal meaning. This research analyzed figurative language in three Eminem’s songs entitled Mockingbird, When I'm Gone, and Zeus to find out the figurative language and the meaning behind it. This research uses a qualitative study that aims to obtain information about figurative language with related theories from Perrine (1992). The Data were collected by using a descriptive qualitative method. It has been found that there are figurative language used to convey meaning in the song, there are simile, metaphor, hyperbole, personification, symbol, and allegory. To conclude the analysis then it can be said that figurative language in the song was used to make the song become more variative and meaningful. Keyword: Semantics, Figurative language, Eminem